Cover Image, Volume 22, Issue 7. Issue 7 (19th June 2020) - Johansson, Lars; Hockings, Paul D.; Johnsson, Eva; Dronamraju, Nalina; Maaske, Jill; Garcia‐Sanchez, Ricardo; Wilding, John P. H.
Abstract : The outside back cover image is based on the Original Article Dapagliflozin plus saxagliptin add‐on to metformin reduces liver fat and adipose tissue volume in patients with type 2 diabetes by John Wilding, Paul Hockings, Lars Johansson et al., https://doi.org/10.1111/dom.14004 .